MICROPLASTS IN FRESHWATER FISH – PROBLEMS AND CHALLENGES: MICROPLASTS IN FRESHWATER FISH – PROBLEMS AND CHALLENGES - Todorova, Polina; Toschkova, Stephany (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The presence of microplastics in the aquatic environment raises concerns about their abundance and potential hazards to aquatic organisms. This review provides insight into the issue that may be of concern to freshwater fish. Plastic pollution is not limited to marine ecosystems; freshwaters also contain plastic particles, as the majority of them enter the oceans via rivers. Microplastics (MPs) can be ingested by fish and accumulate due to their size and poor biodegradability. Furthermore, they have the potential to enter the food chain and cause health problems. Evidence of MP ingestion has been reported in >150 fish species from both freshwater and marine systems. However, the quantification and toxicity of microplastics in freshwater ecosystems are underestimated, ignored and not reported as often as in marine ecosystems. However, their abundance, impact and toxicity in freshwater biota are no less than in marine ecosystems. The interaction of MPs with freshwater fish, as well as the risk of human consumption, remains a mystery. However, our knowledge of the effects of MPs on freshwater fish is still very limited. This study details the state of the toxicity of microplastics (MPs) in freshwater fish. This review will add to our understanding of the ecotoxicology of microplastics on freshwater fish and provide further directions for research.